Preparing England's further education system for zero-carbon construction skills - Killip, G; Robson, J (Emerald Publishing, 2024)
Skills issues for craft trades in building decarbonisation often focus on improving technical knowledge, but known problems of quality assurance in construction also include ‘soft’ employability skills, and the application of sustainability values in practice. New course content is a necessary but not sufficient component of changing practice. The real demand for skills and actual use of skills in the workplace are just as important as new skills supply. A deliberative workshop with 40 expert stakeholders investigated the preparedness of the education and training system for zero-carbon construction skills. Several challenges emerge from this research. The market context for jobs and skills training shows how the over-narrow focus on new courses leads to waste and failures. Policy has an important role to play in developing minimum vocational standards through licensing, allied to consistent, long-term industrial strategy. The low prestige of further education and vocational training hinders real skills development and recruitment and retention of the workforce. Colleges operate with limited resources and competing priorities, creating real constraints on important activities like teacher training. Short courses and continuing professional development have no common standards or link with initial education and training, leading to piecemeal learning of unknown quality.